Variation in perioperative care across centers for infants undergoing the Norwood procedure - Pasquali, Sara K.; Ohye, Richard G.; Lu, Minmin; Kaltman, Jonathan; Caldarone, Christopher A.; Pizarro, Christian; Dunbar-Masterson, Carolyn; Gaynor, J. William; Jacobs, Jeffrey P.; Kaza, Aditya K.; Newburger, Jane; Rhodes, John F.; et al. (The Journal of thoracic and cardiovascular surgery, 2012)
In the Single Ventricle Reconstruction trial, infants undergoing the Norwood procedure were randomly allocated to undergo a right ventricle-to-pulmonary artery shunt or a modified Blalock-Taussig shunt. Apart from shunt type, subjects received the local standard of care. We evaluated variation in perioperative care during the Norwood hospitalization across 14 trial sites. Data on preoperative, operative, and postoperative variables for 546 enrolled subjects who underwent the Norwood procedure were collected prospectively on standardized case report forms, and variation across the centers was described. Gestational age, birth weight, and proportion with hypoplastic left heart syndrome were similar across sites. In contrast, all recorded variables related to preoperative care varied across centers, including fetal diagnosis (range, 55%-85%), preoperative intubation (range, 29%-91%), and enteral feeding. Perioperative and operative factors were also variable across sites, including median total support time (range, 74-189 minutes) and other perfusion variables, arch reconstruction technique, intraoperative medication use, and use of modified ultrafiltration (range, 48%-100%). Additional variation across centers was seen in variables related to postoperative care, including proportion with an open sternum (range, 35%-100%), median intensive care unit stay (range, 9-44 days), type of feeding at discharge, and enrollment in a home monitoring program (range, 1%-100%; 5 sites did not have a program). Overall, in-hospital death or transplant occurred in 18% (range across sites, 7%-39%). Perioperative care during the Norwood hospitalization varies across centers. Further analysis evaluating the underlying causes and relationship of this variation to outcome is needed to inform future studies and quality improvement efforts.